Adaptive HF radio channels based on signal-to-noise ratio using SDR technology - Sorecau, Emil; Sorecau, Mirela; Bechet, Paul (2023 10th International Conference on Modern Power Systems (MPS), 2023)
Adaptive HF (high-frequency) radio channels based on signal-to-noise ratio (SNR) using software-defined radio (SDR) technology is a promising approach to improve the reliability and efficiency of radio communications. The HF radio communication channel is often affected by channel fading, which degrades the signal-to-noise ratio of the received signal. Adaptive techniques can be used to adjust the transmission parameters based on the channel conditions, such as SNR, to mitigate the effects of channel degradation and improve the reliability of HF radio communications. In the paper, we discuss the need for adaptive RF radio channels, the advantages of SDR technology and Python programming combined with the GNU Radio block library. We also propose a specific method for adaptive HF radio channels based on SNR and evaluate this method in the laboratory.